Memutus Rantai Infeksi melalui Fungsi Pengorganisasian Kepala Ruang Rawat - Fitriana Dewi; Hanny Handiyani; Kuntarti Kuntarti (Fakultas Ilmu Keperawatan Universitas Indonesia, 2016)
Perawat berperan penting sebagai pemutus rantai infeksi untuk menurunkan angka kejadian infeksi yang didapat di rumah sakit (HAIs). Penelitian deskriptif korelatif ini bertujuan untuk mendapatkan gambaran pengaruh karakteristik, peran kepemimpinan, dan fungsi manajemen kepala ruang terhadap perilaku perawat dalam memutus rantai infeksi. Penelitian pada 130 perawat menunjukkan faktor yang mempengaruhi perilaku perawat dalam memutus rantai infeksi adalah peran interpersonal (p=0,001; OR=7,07; 95% CI ,.25;22,2), peran pengambilan keputusan (p=0,004; OR=4,7; 95% CI 1,7;13.0), dan fungsi pengorganisasian (p=0,001; OR=21,46; 95% CI 7,2;63,9). Faktor yang paling mempengaruhi perilaku perawat dalam memutus rantai infeksi adalah fungsi pengorganisasian (p=0,001; OR=0,047; 95% CI 0,016;0,139). Kepala ruang berperan sebagai role model untuk meningkatkan pengetahuan dan keterampilan perawat untuk berperilaku baik dalam upaya pencegahan dan pengendalian infeksi di rumah sakit.Abstract Break the Chain Infection by Organization Function Head Ward. Nurses have an important role to break the chain of infection in decreasing Healthcare Associated Infections (HAIs) in hospital. The aim of this descriptive of correlation research is to get the description of characteristic, role of leadership, and the function of head nurse management toward nurse’s behavior in breaking the chain of infection. This research involves 130 nurses showed that the influencing factors of nurse’s behavior (through the quesionnare) in breaking the chain of infection are the interpersonal role (p=0,001, OR=7,07, 95% CI 2,25;22.2), the decision maker role (p=0,004, OR=4,7, 95% CI 1,7;13,0), and the organizing function (p=0,001, OR=21,46, 95% CI 7,2;63,9). The result showed that the dominant factors of the nurse’s behavior in breaking the chain of infection is organizing factors of the head nurse (p=0,001, OR=0,047, 95% CI 0,016;0,139). Head nurse is a role model in increasing the knowledge and skill of nurse to behave well in order to prevent and control the infection in hospital. Keywords: leadership role, management function, nurse’s behavior, prevention and infection control, the chain of infection